Clinical profile of fever in newborn and predictors of outcome - Janakiraman, Deepa; Muthumani, Karthikeyan; Thirumalaikumaraswamy, Sivaraman (International Journal of Contemporary Pediatrics, 2017)
Background: Hyperpyrexia, in neonates is considered as a medical emergency. The aim of the present study was to evaluate complete clinical profile and relevant laboratory investigations in arriving at various etiologies of fever in neonates and to arrive at predictors of mortality among newborns presenting with fever symptoms. Methods: This prospective study conducted in the Neonatology Department of Institute of Child Health and Hospital for Children during the period January 2015 to September 2015. A total of 100 neonates from Day 1 to Day 28 of life regardless of gestational age with fever were included in the study. Complete blood cell counts and blood cultures were obtained on all of the patients. Results: Out of 100 neonates 87% were term new born. Lethargy was the major presenting complaint (48%) associated with fever. Respiratory distress was the most common clinical sign observed in febrile neonates (21%). 63 had a positive septic screening. 16 among those with positive septic screen had an organism grown in the culture. Staphylococcus aureus was the most common organism isolated in febrile neonates. Mortality was seen only in 6% of the neonates who had fever. Conclusion: Children with fever are at higher risk of bacterial infections. They need immediate medical supervision for identification of exact etiology.